Social media usage and health promoting lifestyle in profile related socio-demographic factors in Turkey - Güleç, Dilek (Health Promot Perspect, 2020)
Background: Social media represents a revolutionary new trend that offers opportunities for and threats toward modifying health behaviours. Although social media has considerable health promotion and education tools, this article summarizes the relationship between the health promoting lifestyle and Facebook usage, as Facebook is one of the most popular tools in social media. Methods: We carried out a cross-sectional, descriptive study with 423 Facebook users living in Ankara, Turkey. Nonlinear canonical correlation analysis (OVERALS) was used to describe the complex links between health behaviours, social media usage and demographic characteristics. Results: In this study, a two-dimensional solution with an actual fit measure equal to 0.958was found, and this solution can be interpreted as about 48% of the explained variance. This two-dimensional result shows the relationships and differences between healthy lifestyle subdimensions, social media usage and some demographic characteristics. Conclusion: Using OVERALS, we found evidences supporting associations among social media use, health promoting lifestyle and socio-demographic factors. Further, the complex correlations among these variables were interpreted.